Modulation of Hemostatic Pathways by Breast Cancer Chemotherapy Agents - Swystun, Laura L. (My University, 2011)
Thrombosis is a common complication of chemotherapy for breast cancer patients. However, the specific mechanisms by which chemotherapy agents modulate these hemostatic pathways are not well understood. In this thesis, we investigated the mechanism(s) by which chemotherapy agents can upregulate procoagulant pathways (tissue factor (TF), phosphatidylserine exposure, and cell-free DNA (CFDNA) release) and impair the protein C (PC) anticoagulant pathway. We examined the effects of chemotherapy agents doxorubicin, epirubicin and the cyclophosphamide metabolite acrolein on cell surface procoagulant activity. We found that treatment of endothelial cells with the chemotherapy drugs increased phosphatidylserine exposure and TF activity on treated endothelial cells, blood monocytes and/or smooth muscle cells. This corresponded to an increase in thrombin generation on chemotherapy-treated cells exposed to recalcified, defibrinated plasma. We also found that found that doxorubicin and epirubicin can increase CFDNA release from breast cancer chemotherapy patients and healthy mice, which corresponds to an increase in thrombin-antithrombin levels. Treatment of venous whole blood and isolated neutrophils with doxorubicin and epirubicin increased CFDNA release. We found that exposure of recalcified plasma to CFDNA isolated from epirubicin-treated whole blood increased thrombin generation by activating the contact pathway. We investigated the effects of chemotherapy on the PC anticoagulant pathway. We found that acrolein decreased EPCR while increasing thrombomodulin expression on treated endothelial cells. A corresponding decrease in activated PC generation was measured on acrolein-treated endothelial cells exposed to recalcified, defibrinated plasma. Healthy mice treated with acrolein and cyclophosphamide increased PC antigen levels, but no measurable increase in plasma APC levels. Breast cancer chemotherapy drugs elevate thrombin generation by activating coagulation through the TF and contact pathways, and by promoting phosphatidylserine exposure, as well as by impairing PC activation EPCR expression. These studies provide insight into the mechanisms of breast cancer chemotherapy-induced hypercoagulation.
Keywords: thrombosis; cancer; chemotherapy; thrombin generation; tissue factor; protein C pathway; Hemic and Lymphatic Diseases; Hemic and Lymphatic Diseases